TECHNOLOGY ENHANCED MENTORSHIP FOR PERSONS WITH DISABILITIES - Kumar, Anil; Trique, Mohammed; Hasan, Ansarul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Mentorship acts as a significant stimulator for the personal and professional development of an individual. In educational and professional life of an individual, various desires of a person can be fulfilled through right kind of mentorship process. A lot of potential of a person usually remains hidden in traditional situations but mentorship provides a platform for individuals including PwDs, to utilise their potential up to optimum level. In comparison to normal persons, PwDs face certain unique barriers associated with them e.g. educational barriers, employment issues and social exclusion. For removing these barriers mentorship is of great importance as it has been observed that through mentorship sessions we can provide performing platforms that are best suited to them. There are certain limitations of traditional mentorship models in the context of PwDs with respect to infrastructure, geographical and accessibility related issues. In such situations technology plays a crucial role in the form of varied mentorship sessions for the persons belonging to PwDs category; as through the application of technology the gaps of traditional mentorship can be fulfilled by providing accessible, inclusive and equitable opportunities. The present paper being conceptual in nature is an attempt to explore the role of technology in providing the best suited mentorship in the context of PwDs. The paper explores the role of digital platforms, assistive technologies and tools like AI, Virtual reality and Augmented Reality in the creation of impactful mentorship experiences for the PwDs. The paper concludes with the benefits like flexibility, personalised learning experiences and increased connectivity, can be ensured with the help of technology-enhanced mentorship.